Signaling Pathway and Transcriptional Regulation in Osteoblasts during Bone Healing: Direct Involvement of Hydroxyapatite as a Biomaterial - Junaidi Khotib; Maria Apriliani Gani; Aniek Setiya Budiatin; Maria Lucia Ardhani Dwi Lestari; Erreza Rahadiansyah; Chrismawan Ardianto (MDPI AG, 2021)
Bone defects and periodontal disease are pathological conditions that may become neglected diseases if not treated properly. Hydroxyapatite (HA), along with tricalcium phosphate and bioglass ceramic, is a biomaterial widely applied to orthopedic and dental uses. The in vivo performance of HA is determined by the interaction between HA particles with bone cells, particularly the bone mineralizing cells osteoblasts. It has been reported that HA-induced osteoblastic differentiation by increasing the expression of osteogenic transcription factors. However, the pathway involved and the events that occur in the cell membrane have not been well understood and remain controversial. Advances in gene editing and the discovery of pharmacologic inhibitors assist researchers to better understand osteoblastic differentiation. This review summarizes the involvement of extracellular signal-regulated kinase (ERK), p38, Wnt, and bone morphogenetic protein 2 (BMP2) in osteoblastic cellular regulation induced by HA. These advances enhance the current understanding of the molecular mechanism of HA as a biomaterial. Moreover, they provide a better strategy for the design of HA to be utilized in bone engineering.